Kinetics and Mechanism of Oxidation of Benzyl Alcohol by Benzimidazolium Fluorochromate - J. Dharmaraja; K. Krishnasamy; M. Shanmugam (E-Journal of Chemistry)
The kinetics of oxidation of benzyl alcohol (BzOH) by benzimidazolium fluorochromate (BIFC) has been studied in 50% aqueous acetic acid medium at 308 K. The reaction is first order with respect to [oxidant] and [benzyl alcohol]. The reaction is catalysed by hydrogen ions. The decrease in dielectric constant of the medium increases the rate of the reaction. Addition of sodium perchlorate increases the rate of the reaction appreciably. No polymerization with acrylonitrile. The reaction has been conducted at four different temperature and the activation parameters were calculated. From the observed kinetic results a suitable mechanism was proposed.